Arcobacter - an emerging threat to animals and animal origin food products? - Hussain Shah , Sayed Atta; Abdul Aziz, Saleha; Zakaria, Zunita; Marimuthu, Murugaiyah (Elsevier, 2011)
Genus Arcobacter is consisted of twelve species, which have been isolated from a wide range of animals and animal origin food products such as beef, milk, rabbit meat, pork and chicken, thus raising public health concern. Recent reports showed that infection in human can occur by close contact with pets (dogs and cats). Dose response, pathogenicity and toxin production in the development of disease are not fully understood. As cultural detection is time consuming and not confirmatory, various DNA based protocols have been developed for rapid and accurate identification of Arcobacter species. This review reports on the occurrence of Arcobacter in animals other than chickens and in food of animal origin other than chicken meat.